Bioactivity of Sauropus androgynus and Elephantopus scaber to CD4+IL2+ and CD4+IL4+ T Cells Modulation in Balb/c Pregnant Mice Model of Typhoid - Fuadah, Yayu Tsamrotul; Djati, Moch. Sasmito; Widyarti, Sri (The Journal of Experimental Life Science, 2015)
Pregnant woman have higher risk to get infection, because pregnancy decreasing the cell T activity. Sauropus androgynus and Elephantopus scaber has substance like saponin and flavonoid which has been well known as natural imunomodulator, particularly to increase amount of immunocompetent cell. This research is important to recognize effective supplement supply for immunomodulator of S. androgynus and E. scaber to increase mice's (Mus musculus Balb/c) immune system. This research conducted in seven treatments by 3 repetitions for each treatment by using pregnant mice which has been infected by bacteria Salmonella typhimurium (dose 107 CFU.mL-1). Bacteria are injected to mice intraperitoneal in day 5th after giving combination of extract E. scaber and S. androgynus. The dose of E. scaber and S. androgynus combination are 200; 150:37.5; 100:75; 50: 112.5; 150. Five group of treatment were infected by S. typhimurium. Two other groups were the control, namely negative control which was only given NaCMC 0.05% without infection and positive control which was given NaCMC 0.05% and infected by S. typhimurium. After being injected, treatment was redone till the day of surgery. The surgery was executed in day 12th and 18th of pregnancy. Data were analyzed using ANOVA (p < 0.05) and Duncan test. Result indicated that extract of S. androgynus and E. scaber could increase amount of immune system in pregnant mice. This was indicated from significant increasing in amount of cell T CD4+IL2+ and CD4+IL4+ in pregnant mice which has been infected by S. thypimurium. Formula of extract S. androgynus and E. scaber which could return immune condition was approached condition of healthy pregnant mice such as E. scaber 200 mg.kg-1 BW; E. scaber 100 mg.kg-1 BW and S. androgynus 75 mg.kg-1 BW; E. scaber 50 mg.kg-1 BW and S. androgynus 112.5 mg.kg-1 BW; and S. androgynus 150 mg.kg-1 BW, respectively. Keywords: CD4+IL2+,CD4+IL4+, E. scaber, Immunomodulator, S. androgynus, S. typhimurium